Activity of ethanolic extracts leaves of Machaerium floribundum against acne-inducing bacteria, and their cytoprotective and antioxidant effects on fibroblast - Díaz, Lorena (2011)
Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus have been recognized as the bacteria that are involved in the inflammatory process of acne, while oxidants and antioxidants are involved in the repair of cutaneous tissue affected. In this study an evaluation was made of the antibacterial effect by the agar diffusion and broth dilution method, the cytoprotective and antioxidant effect on 3T3 dermic fibroblast cells, treated with hydrogen peroxide and the scavenging capacity of free radicals was determined by the 2, 2-diphenyl-l-picrylhydrazyl (DPPH) method as well as the Reducing Power of the ethanolic extracts of the leaves of the Machaerium floribundum. Minimal bactericidal concentrations (MBC) were obtained against Propionibacterium acnes and Staphylococcus aureus of 5 mg/mL and 2 mg/mL, respectively. A cytoprotective effect of 111% was observed over the cellular viability of the fibroblasts at 10 μg/mL and an antioxidant effect of 92% over the viability of the fibroblasts treated with hydrogen peroxide at 25 μg/mL. A stimulation of 24% growth of fibroblasts at 50 μg/mL was evidenced. On the other hand a 93% scavenging activity of the DPPH free radical was shown for 100 μg/mL with a CI50 of 34 μg/mL. The reducing power was evidenced to be dependent on the concentration. The results obtained indicated that the ethanolic extract of Machaerium floribundum shows a good antibacterial activity against bacteria that induce acne and a high potential for scavenging of free radicals at relatively low concentrations.